The effects of dramatization method on elementary school students' levels of maths attidutes and achivements - (:unkn) unknown (ELSEVIER SCIENCE BV, 2009)
The aim of this study is to investigate the effects of dramatization method on elementary school students' levels of Math's attitudes and achievements. The research is carried out on total 69 students who are in 8(th) year of elementary school in Istanbul, Anatolian side, and it is continued during the unit Trigonometry. The lessons are taught traditionally to control group whereas the lessons are taught by using dramatization method in experimental group. Before the research started, pre-test and Math's attitudes questionnaire applied to control and experimental group. At the end of the study, same tests were used again. According to the results of achievement pre-test, post-test and t-test, it is found out that dramatization method is effective on both students' math's achievement and the level of attitudes. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Attitude; dramatization; Math's education; achievement; trigonometry